KURIKULUM CINTA SEBAGAI PENDEKATAN HUMANISTIK DALAM PENDIDIKAN AGAMA ISLAM - Katijah; Zaitun; Windayani (An-Nahdlah: Jurnal Pendidikan Islam, 2026)
Islamic Religious Education continues to face challenges related to the dominance of cognitive and normative approaches, which often cause religious values to remain at the level of knowledge rather than being internalized into students’ attitudes and behaviors. Along with the implementation of the Merdeka Curriculum, the Ministry of Religious Affairs introduced the Love-Based Curriculum as a value-oriented approach emphasizing compassion, empathy, tolerance, and humanity in the learning process. This article aims to examine and conceptualize the Love-Based Curriculum as a humanistic approach in Islamic Religious Education. This study employs a qualitative approach with a conceptual literature-based design, analyzing national and international scholarly sources published within the last five years as well as relevant educational policy documents. The findings indicate that the Love-Based Curriculum functions as a pedagogical approach that integrates values of love into learning relationships, habitus formation, and institutional culture. This approach addresses the limitations of formalistic Islamic education by promoting meaningful learning and contextual value internalization. The study concludes that the Love-Based Curriculum offers a significant contribution to the development of more humanistic, ethical, and contextually relevant Islamic Religious Education, although further empirical research is needed to validate its implementation and impact.